Pengaruh Inflasi dan Suku Bunga (BI Rate) terhadap Profitabilitas (ROA) Perbankan di BEI Tahun 2021-2022 - Henny Kumalasari Widodo; Sri Yulianingsih; Dwi Astutik (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2022)
There are differences in the influence of inflation and interest rates on profitability (ROA) in banks that fall into categories on the IDX. Objectives: 1. Determine whether interest rates can partially influence profitability (ROA). 2. Determine whether inflation can partially influence profitability (ROA). 3. Determine how the inflation rate and interest rates (Bi Rate) affect profitability (ROA) simultaneously. This elitism in testing is carried out to determine the influence when inflation and interest rates occur which can affect profitability (ROA) in banking. In this research the researcher used the Associative Research method. The samples taken in the research carried out were 4 banks registered on the IDX. Results: 1. Interest rates have a partial effect on profitability (ROA). 2. Inflation also partially influences profitability (ROA). 3. Inflation and interest rates simultaneously have an influence, namely simultaneously on profitability (ROA).